Herlitz Junctional Epidermolysis Bullosa with a Novel Mutation in LAMB3. Issue 4 (26th December 2012) - Kittridge, Ashley; Patel, Riddhi; Novoa, Roberto; Tamburro, Joan
Abstract Herlitz junctional epidermolysis bullosa (H‐JEB) is a rare, heritable mechanobullous disease that affects infants at birth and causes early death. This disease is primarily caused by compound heterozygous or homozygous mutations in one of three genes affecting the function of one of the three chains of the laminin‐332 (formerly laminin‐5) protein. Here we report a case of H‐JEB with a novel heterozygous mutation in LAMB3, c.1597G>A (p.Ala533Thr). These findings attest to the molecular heterogeneity of JEB and emphasize the importance of genetic analysis to help make an accurate diagnosis, predict clinical prognosis, and identify phenotypic‐genotypic relationships that may aid in prenatal diagnosis and genetic counseling for the future.